Adult Education as Snake Oil under the Guise of Democracy - Alison A. Carr-Chellman; Davin J. Carr-Chellman (Adult Education Research Conference, 2001)
Based on initial content analysis research into the semiotics of advertising for online learning, this paper extends our understanding of the commodification of education via the web by carefully examining the implications of this marketing on the goals of democracy, the just distribution of education and knowledge as resources, and the consequent impact on social justice and equity.